2021
DOI: 10.1126/sciadv.abj0512
|View full text |Cite
|
Sign up to set email alerts
|

Lef1 restricts ectopic crypt formation and tumor cell growth in intestinal adenomas

Abstract: Lef1 is induced in intestinal adenomas, in which it restricts ectopic crypt formation and tumor growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 84 publications
(157 reference statements)
0
11
0
Order By: Relevance
“…Our results clearly indicated that resveratrol inhibited LEF1 mRNA and protein levels and reduced transcription of Wnt‐related genes (MYC). Considering previous studies, 16,17,34,39–42 we suggest that resveratrol inhibits LEF1 expression and thereby suppresses the transcription of Wnt‐related genes, leading to the inhibition of adenoma formation, although there is a contradictory study regarding LEF1 function 35 …”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…Our results clearly indicated that resveratrol inhibited LEF1 mRNA and protein levels and reduced transcription of Wnt‐related genes (MYC). Considering previous studies, 16,17,34,39–42 we suggest that resveratrol inhibits LEF1 expression and thereby suppresses the transcription of Wnt‐related genes, leading to the inhibition of adenoma formation, although there is a contradictory study regarding LEF1 function 35 …”
Section: Discussionmentioning
confidence: 79%
“…LEF‐1 directly interacts with β‐catenin and serves as transcription factor LEF‐1/TCF, which promotes transcription of Wnt‐responsive target genes, indicating the pivotal role of LEF1 in the Wnt/β‐catenin signaling pathway in CRA. LEF‐1 is reported to be induced by Wnt‐signal activation including Apc and β‐catenin mutations (accumulation) during colorectal carcinogenesis 34,35 . Moreover, the K‐RAS mutation reportedly induces LEF‐1 expression in human and murine colorectal tumors 36 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To study the effect of BVDU on Apc ‐driven oncogenic transformation in vivo , we first used Villin‐Cre ERT2 ; Apc fl / fl mice to activate epithelial‐wide recombination of Apc alleles in the intestine. As previously reported, upon injection of tamoxifen, these mice develop massive hyperproliferation throughout the epithelium followed by rapid death within a week (Heino et al , 2021). We injected two doses of 2 mg tamoxifen on two consecutive days, either in the presence or absence of BVDU (400 mg/kg), which was administered daily via oral gavage.…”
Section: Resultsmentioning
confidence: 99%